The effect of relative humidity on the behaviour and development of Triatoma brasiliensis - Guarneri, A.A. (2002)
The preference for relative humidity (RH) and suitability of different levels of this environmental parameter were investigated in the haematophagous bug Triatoma brasiliensis Neiva, 1911 (Hemiptera, Reduviidae). The hygropreference of T. brasiliensis was studied using a RH gradient and the effect of different RHs on the egg hatching, nymph mortality and moulting success was also analysed. The results show that egg hatching in first-instar nymphs of T. brasiliensis was lower at extreme RHs and, particularly, it was lowest at 9.3% RH. The survival of starved nymphs was not affected by RH, but the percentage of engorged nymphs and the ecdysis success of these nymphs once fed was diminished strongly by high humidity. Fourth-instar nymphs preferred to stay at the lowest RH during the first 5 days after feeding and during ecdysis. This preference changed markedly during starvation. Fifteen days after ecdysis, the bugs moved towards intermediate humidities, and 30 days after ecdysis they even preferred the most humid sectors of the gradient. Females preferred to lay eggs in dry environments, suggesting that they may not have a particular hygropreference for oviposition, but that they simply lay their eggs at the RHs where they prefer to stay.